Economic Effectiveness of Technogenic Mineral Formations Management as a Factor of Mineral Raw Material Basis Restoration of Kazakhmys Enterprises - SEIDUALIN, Darken; ABDRAMANOVA, Gulzhan; MUSSINA, Kamshat; MUKANOV, Aidar; YESSENBAYEVA, Ainur; OMAROVA, Kenzhegul; PODSUKHINA, Olga (Journal of Environmental Management and Tourism, 2018)
The problems of the raw material base depletion, ineffective technological chain of ores mining and processing with a high loss factor require a systematic, sound approach to the future development of the Zhezkazgan region. The conducted monitoring of ore fields and tailings is represented by significant stocks of technogenic formations. As a methodology for research works at the mines of Kazakhmys enterprises a method of geotechnological work was chosen. Based on various physical and chemical impacts, the rocks are brought into a mobile state and receive useful components from hard-to-digest ores. In the extraction process, X-ray radiometric methods are used, which allow ore separation and mixing at the ore preparation stage, thereby reducing the yield of unpromising ores to the surface and increasing the multispectral nature of the extracted components. The created experimental furnace of chlorinating firing makes it possible to extract valuable components in the form of additional products such as rhenium, gold, iron from complex products of rough concentrate, which due to the lack of effective technology went to the tailings of enrichment. The applied geotechnology is environmentally balanced, since the waste that is not of economic value can be used as raw material in the construction industry. The uniqueness of the research work is in detailed spectral analysis of the physical and chemical properties of technogenic formation and poor ores of the Zhezkazgan region, using technological processes for extracting associated components from waste and decommissioned ores by the method of chlorinating roasting and obtaining an additional solution with a high content of the useful component.